2021
DOI: 10.1136/gutjnl-2020-323585
|View full text |Cite
|
Sign up to set email alerts
|

HCV genome-wide analysis for development of efficient culture systems and unravelling of antiviral resistance in genotype 4

Abstract: ObjectiveHCV-genotype 4 infections are a major cause of liver diseases in the Middle East/Africa with certain subtypes associated with increased risk of direct-acting antiviral (DAA) treatment failures. We aimed at developing infectious genotype 4 cell culture systems to understand the evolutionary genetic landscapes of antiviral resistance, which can help preserve the future efficacy of DAA-based therapy.DesignHCV recombinants were tested in liver-derived cells. Long-term coculture with DAAs served to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Using a chimeric JFH1-replicon in which NS5A originates from GT4r, Nguyen et al 52 reported that L31M and Y93H confer resistance to LDV. Pham et al 58…”
Section: Hcv-genotype 4 and The Emergence Of Viral Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…Using a chimeric JFH1-replicon in which NS5A originates from GT4r, Nguyen et al 52 reported that L31M and Y93H confer resistance to LDV. Pham et al 58…”
Section: Hcv-genotype 4 and The Emergence Of Viral Resistancementioning
confidence: 99%
“…[79][80][81] Attempts to develop infectious models for other genotypes and subtypes made very limited success and unlike JFH1, all other isolates require cell-culture adaptation changes 82 as illustrated with the case of available GT4-based HCVcc. 58,83 The first model system was established by constructing a full-length ED43 and several mutants harboring ED43's replication-enhancing mutations (REM). 83 The introduction of these full-length constructs into Huh7.5.1 cells followed by a long-term passaging revealed additional mutations only for two clones releasing HCV core particles in the culture medium.…”
Section: Cell Culture-derived Hcvmentioning
confidence: 99%
See 3 more Smart Citations